Atores e valores: o processo de readequação do espaço físico da Casa de Câmara e Cadeia de Mariana - Fernanda Trindade de Carvalho (2012)
The present study has as main focus the debate about the values imputed to the Mariana Town-Council by different social groups: surrounding residents, meetings participants, heritage agents and tourists. The study has been initiated from the perception of insufficient physical space to house all the institution activities and the evident necessity of restoration. Due to the possibility of intervention, the understanding of the social relations established in the Town-Council and in the scenario in which the institution is located - Minas Gerais Square - became necessary. The investigation has started by the understanding of the facts that make the Mariana Town-Council and Jail relevant under the historical-cultural aspect. The study is also based on the actual concept imputed to the term heritage and in the theory of values proposed by Aloïs Riegl and reasserted by the The Burra Charter from The Australian National Commitee of ICOMOS. It assumes that any intervention process in a heritage must go beyond the physical structure, it is required a study about values attributed to the heritage by various society segments, and not only by technicians anymore.